2014
DOI: 10.1002/ppul.23095
|View full text |Cite
|
Sign up to set email alerts
|

Increased T cell activation in BALF from children with Mycoplasma pneumoniae pneumonia

Abstract: Increased activation of T cell in BALF may play an important role in the inflammatory response of acute and severe MPP. IL-6 may predict the severity and prognosis and provide a better assessment for patient care. However, the underlying mechanism awaits further detailed investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 32 publications
2
48
0
Order By: Relevance
“…Mycoplasma pneumoniae pneumonia has an increase of neutrophils and IL-6, especially in severe group. Compared to acute stage, a decreased percentage of neutrophils and IL-6 level was observed at the recovery stage in children with severe Mycoplasma pneumoniae pneumonia [155]. However, treatment with prednisolone or cyclosporin-A leads to marked neutrophils and exudates in the alveolar lumen.…”
Section: Neutrophils In Infectious Pneumoniamentioning
confidence: 99%
“…Mycoplasma pneumoniae pneumonia has an increase of neutrophils and IL-6, especially in severe group. Compared to acute stage, a decreased percentage of neutrophils and IL-6 level was observed at the recovery stage in children with severe Mycoplasma pneumoniae pneumonia [155]. However, treatment with prednisolone or cyclosporin-A leads to marked neutrophils and exudates in the alveolar lumen.…”
Section: Neutrophils In Infectious Pneumoniamentioning
confidence: 99%
“…It causes up to 40% of community-acquired pneumonia (CAP) cases in children and as much as 18% of cases requiring hospitalization; these percentages are even higher during epidemics 24. The incidence of Mycoplasma pneumoniae pneumonia (MPP) has been increasing in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 was also associated with pleural effusion [20] and radiological appearance [8] in MPP patients. Guo L et al reported that IL-6s in serum of patients infected by the macrolide-resistant strains were higher than those infected by non macrolide-resistant strains [21] . Therefore IL-6 was closely related to MPP.…”
Section: Discussionmentioning
confidence: 99%